Flexible TPU pneumatic actuator simulation - San Martin Lopez, Julio Cesar (2022)
Actuators are devices that provides a controlled change in a physical system. They can operate manually, electrically, or by various fluids. Among them, pneumatics actuators have advantages of working with compressible fluids that provides safety and efficient limitations. These are very critical parameters for soft robotics. Rigid actuators are not suitable to substitute muscle functions, hence flexible actuators are appealing. Yet the process to fabricate soft actuators have long iteration until the final product is manufactured and is difficult to design and control due to their natural flexible behavior. 3D printing could be a possible solution. Researchers are exploring feasible solutions with 3D printing material. However, since it’s a new area of research, there is not a large and deep characterization of these materials. This study will focus on the simulation of a hyperelastic TPU model based on experimental data. Simulations were done utilizing the software ANSYS to characterize the behavior on mentioned model for a soft actuator usage. The results were consistent when the printing orientation of actuators was parallel (0°) to the strain direction of the actuators. Results were less consistent when utilizing a printing orientation of 45° or higher.